Penerapan Pendekatan Teks Multimodal untuk Meningkatkan Keterampilan Mengajar Guru Bahasa Indonesia di Kota Palu - Ferdiawan, Ferdiawan; Maulidi, Ahmad; Sahril, Sahril (Paedagogie, 2026)
This study aims to analyze the effectiveness of implementing a multimodal text approach in enhancing the teaching skills of Indonesian language teachers in Palu City. The multimodal text approach, which integrates visual, verbal, audio, and digital modes, is considered relevant to the demands of 21st-century learning and the Merdeka Curriculum that emphasizes creativity, interaction, and meaningful learning experiences. This research employed a descriptive qualitative method involving Indonesian language teachers at the junior high school level in Palu City as key informants. Data were collected through in-depth interviews, classroom observations, and analysis of supporting documents. The findings reveal that the use of multimodal texts has a positive impact on both the learning process and teachers’ instructional skills. Teachers become more creative, adaptive, and innovative in designing learning activities, as well as more capable of addressing students’ diverse learning needs. Learning becomes more engaging, interactive, and easier to understand through the support of visual, audio, and digital media. Additionally, the study identifies three emerging teacher habits: resilience in dealing with technological limitations, adaptability to digital changes, and transformative attitudes in developing more relevant and contextual teaching practices. However, several challenges persist, including limited technological devices, power disruptions, and unequal digital proficiency among teachers. Overall, the study confirms that the multimodal text approach is an effective strategy for improving the teaching skills of Indonesian language teachers and enhancing the quality of learning in the digital era. These findings are expected to serve as a reference for schools and policymakers to strengthen teacher competencies through adequate training and technological support.